Influence of Pyrethroid Resistance on Vector Competency for Zika Virus by Aedes aegypti (Diptera: Culicidae). Issue 4 (16th March 2021) - Parker-Crockett, Casey; Connelly, C Roxanne; Siegfried, Blair; Alto, Barry
Abstract: The vector competence of mosquitoes for pathogens has been shown to be influenced by the status of insecticide resistance in the mosquito population. However, to date, only two studies has explored the impact of insecticide resistance on arbovirus transmission. The global and widespread use of pyrethroids has led to the development of insecticide resistance in many mosquito species, including Aedes aegypti (Linnaeus) (Diptera: Culicidae), the primary vector of Zika virus. Strains of Ae. aegypti that were genetically similar, but responded differently to pyrethroid exposure, were developed using backcrossing techniques. These populations were orally infected with Zika virus and susceptibility to infection, disseminated infection, and transmission potential were evaluated. Analyses revealed differences in susceptibility to infection and disseminated infection between the pyrethroid susceptible and resistant strains of Ae. aegypti during the infection period. Here, we identify an additional challenge to that of widespread pyrethroid resistance. Specifically, resistance is associated with altered phenotypic traits that influence susceptibility to arbovirus infection and progression of infection in the mosquito, factors which ultimately influence risk of arbovirus transmission. These findings support the need to 1) consider insecticide resistance status during times of arbovirus transmission and 2) to implement insecticide resistance management/ mitigation strategies in vector control programs.